Improving the optical and thermoelectric properties of Cs2InAgCl6 with heavy substitutional doping: a DFT insight - Bhamu, K. C.; Haque, Enamul; Praveen, C. S.; Kumar, Nandha; Yumnam, G.; Hossain, Md. Anwar; Sharma, Gautam (RSC Advances, 2021)
The next-generation indium-based lead-free halide material Cs2InAgCl6 is promising for photovoltaic applications due to its good air stability and non-toxic behavior. However, its wide bandgap (>3 eV) is not suitable for the solar spectrum and hence reduces its photoelectronic efficiency for device applications. Here we report a significant bandgap reduction from 2.85 eV to 0.65 eV via substitutional doping and its effects on the optoelectronic and opto-thermoelectric properties from a first-principles study. The results predict that Sn/Pb and Ga and Cu co-doping will enhance the density of states significantly near the valence band maximum (VBM) and thus reduce the bandgap via shifting the VBM upward, while alkali metals (K/Rb) slightly increase the bandgap. A strong absorption peak near the Shockley-Queisser limit is observed in the co-doped case, while in the Sn/Pb-doped case, we notice a peak in the middle of the visible region of the solar spectrum. The nature of the bandgap is indirect with Cu-Ga/Pb/Sn doping, and a significant reduction in the bandgap, from 2.85 eV to 0.65 eV, is observed in the case of Ga-Cu co-doping. We observe a significant increase in the power factor (PF) (2.03 mW m(-1) K-2) for the n-type carrier after Pb-doping, which is similar to 3.5 times higher than in the pristine case (0.6 mW m (-1) K-2) at 500 K.

Functionalized Mo2BX2 (X = H, OH, O) MBenes as a promising sensor, capturer and storage material for environmentally toxic gases: A case study of 1T and 2H phase - Shukla, Aarti; Sharma, Gautam; Krishnamurty, Sailaja (Applied Surface Science, 2023)
MBenes analogous to MXenes, exfoliated from the bulk MAB phase (M = transition metal, A = IIIA and IVA group, and B = boron) have appeared as promising two dimensional (2D) materials due to their intriguing properties. Here, we report the 2D 1T-2H-phase of Mo2B with their functionalized derivatives Mo2BX2 (X= H, OH, O) and investigate their structural, electronic, and adsorption behavior of toxic gases using the first-principles calculations. This study finds that pristine and functionalized MBenes have dynamic and thermal stability and possess metallic nature in both phases. Based on adsorption behavior and comparison with other 2D materials, we find that pristine MBenes are a desirable adsorbent for NO2, SO2, and CO2 capture. In contrast, the moderate adsorption energies for functionalized MBenes-NH3 systems reveal good sensitivity for NH3 gas detection in both phases. In particular, 2H-Mo2BH2 has higher CT (-0.11e) and appropriate adsorption energy (-0.30 eV), leads a shorter recovery time. Further, DOS calculations reveal that the electrical conducting behavior of MBenes makes them suitable for NH3 detection with a short recovery time. Our results would provide the first insight into the surface-functionalized effect on the structural and electronic properties of the MBenes, and shed light on the application of MBenes for the sensing and catalyst of typical toxic and greenhouse gases, respectively.
Keywords: Adsorption energy; First-principles study; Functionalization; Gas sensing; MBenes